Does the frequency of eating snacks increase food waste? A study based on senior high school in China - Zhang, Panpan; Zhang, Weijie; Liu, Xiaojie; Sun, Fangyuan (Frontiers in Sustainable Food Systems, 2024)
Food waste is increasingly becoming a global challenge, and school canteens are a significant and severe source of food waste. Reducing food waste is conducive to ensuring food security and environmental sustainability. A good understanding on the influencing factors of food waste is a prerequisite for exploring effective measures to reduce food waste. We obtained senior high school first-hand food waste data through field survey using the methods of face-to-face interview, questionnaire survey, and direct weighing in September 2019. Our survey data showed that the per capita per meal food waste of senior high school students (SHSS) was 44.48 g. The specific performance was as follows: the per capita per meal food waste of breakfast, lunch, and dinner was 22.39, 55.28, and 54.24 g, respectively. The empirical results showed that the frequency of eating snacks had a significant effect on whether the SHSS had food waste behavior and significantly affected the amount of food waste by SHSS. With the increased frequency of eating snacks, the food waste probability was increased and the amount of food waste was greater. This study suggested that we could eat snacks but reduced the frequency of eating snacks to achieve the goal of mitigating food waste. This was a simple and effective way to reduce food waste.